How augmented reality could improve the student’s attraction to learn mechanisms - Boboc Răzvan Gabriel; Chiriac Rareș-Lucian; Antonya Csaba (My University, 2021)
Mechanics, along with electronics, is a basic field for the development of high technologies. However, learning mechanics is not an easy task. To meet and adapt to the requirements of students in the digital age, teachers must provide them significant ways to incorporate the latest technologies and applications for their studies. In this study, we explored the application of augmented reality (AR) to improve the learning of the science of Mechanisms. An AR application was implemented and developed for Android-based devices, followed by a qualitative experiment conducted with a sample of 116 students. The study was based on the technology acceptance model and the students’ attitudes towards learning in AR environments were assessed using the structural equation modeling. The results showed that the didactic potential of this application is promising, which is highlighted by the positive attitude about using the application, as well as by the high values obtained for intention to use.